Developing Early ChildrenÃ¢â‚¬â„¢s Creativity Through Ã¢â‚¬Å“BatikÃ¢â‚¬Â Painting Activities in Pembina State Kindergarten of Pekalongan - Nisa, Dwiana Zahiratun; Mukminin, Amirul (Universitas Negeri Semarang, 2014)
Batik is one of the activities associated with patience, precision, and patience to obtain a maximum result, in addition to the quality batik influenced by the parts of the creativity. One way to preserve the culture of batik and develop the creativity of children through learning activities can be done in batik activities that have been adapted to the childÃ¢â‚¬â„¢s development. Formulation of the problem in this study is whether the activities of batik can develop creativity early childhood. The approach in this study experimental pretest and posttest control group design. The population in this study is a kindergartener State coach Pekalongan aged 5-6 years, as many as 30 children Kindergarten State Trustees Western District of Pekalongan as the experimental group of 30 children and kindergarten Pembina State of North Pekalongan as the control group. T-test analysis of the calculation of posttest between the experimental and control groups generate 14,089 tcount > table of 2,045. Sig (2-tailed) <0.05 ie 0.00<0.05. It shows that Ho is rejected and Ha accepted. The average or mean value of 21 433 posttests. Based on these calculations, it can be concluded that the activities of batik can develop the creativity of children in the experimental group pretest and posttest, as well as batik activities can not develop creativity early childhood on the pretest and posttest in the control group. This shows batik activities that have been adapted to the development of effective early childhood used to develop creativity.How to citeNisa, D., & Mukminin, A. (2014). Developing Early ChildrenÃ¢â‚¬â„¢s Creativity Through Ã¢â‚¬Å“BatikÃ¢â‚¬Â Painting Activities in Pembina State Kindergarten of Pekalongan. Indonesian Journal Of Early Childhood Education Studies, 3(2), 139-142. doi:10.15294/ijeces.v3i2.9488